[HSO3-pmim][CH3SO3] as an Efficient Catalyst for the Synthesis of 1,5-Benzodiazepine Derivatives under Ultrasound Irradiation - Li, Cheng; Hao, Qing-Hong; Liu, Hai-Yan; Wang, Chun; Ma, Jing-Jun; Zhu, Wen-Gang (Asian Journal of Chemistry, 2013)
1,5-Benzodiazepine derivatives were synthesized in moderate to excellent isolated yields by the condensation reactions of o-phenylenediamine and ketones catalyzed by [1-methyl-3-(3-sulphopropyl)imidazolium methyl sulphate] under ultrasound irradiation using n-hexane as solvent. This method is simple, effective and gives better yields.